2023
DOI: 10.17221/96/2023-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

An update about beneficial effects of medicinal plants in aquaculture: A review

F Dadras,
J Velisek,
E Zuskova

Abstract: Aquaculture is an essential and growing component of agricultural and global ecosystems worldwide. Aquaculture provides more than 25% of the total aquatic food consumption by humans. The development of the aquaculture industry should be followed in successive industrial years, and therefore it is necessary to pay attention to the management and type of farming system that is compatible with the environment. The use of antibiotics for disease control has been criticised for their negative effects, including the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 161 publications
(323 reference statements)
0
2
0
Order By: Relevance
“…The specific immune system is activated when the innate immune system is overwhelmed, and it includes antibodies and cell-mediated responses. There is growing evidence that herbs can have a positive impact on the immune response of fish [ 22 ]. For example, a study by [ 23 ] found that the long-term feeding of herbs to fish resulted in an increase in serum total protein, haemato-biochemical, and humoral responses.…”
Section: Discussionmentioning
confidence: 99%
“…The specific immune system is activated when the innate immune system is overwhelmed, and it includes antibodies and cell-mediated responses. There is growing evidence that herbs can have a positive impact on the immune response of fish [ 22 ]. For example, a study by [ 23 ] found that the long-term feeding of herbs to fish resulted in an increase in serum total protein, haemato-biochemical, and humoral responses.…”
Section: Discussionmentioning
confidence: 99%
“…The use of natural extracts as dietary supplements or additives in aquafeeds holds great promise for improving the health and performance of farmed fish. By reducing oxidative stress and enhancing antioxidant defences, these extracts may contribute to improved growth, immunity, and stress tolerance in aquatic species (Dügenci et al, 2003;Xavier et al, 2020;Dadras et al, 2023;Quagliardi et al, 2024). In addition, the potential role of GC extracts in preserving the quality and shelf-life of fish products warrants further investigation, as this may have implications for fisheries management and seafood industry practices (Hasan et al, 2021).…”
Section: Activities Of Antioxidant Enzymes Inmentioning
confidence: 99%